Cross‐species genetics converge to TLL2 for mouse avoidance behavior and human bipolar disorder. (12th July 2013) - de Mooij‐van Malsen, J.G.; van Lith, H.A.; Laarakker, M.C.; Brandys, M.K.; Oppelaar, H.; Collier, D.A.; Olivier, B.; Breen, G.; Kas, M.J.
Abstract : Interspecies genetic analysis of neurobehavioral traits is critical for identifying neurobiological mechanisms underlying psychiatric disorders, and for developing models for translational research. Recently, after screening a chromosome substitution strain panel in an automated home cage environment, chromosomes 15 and 19 were identified in female mice for carrying genetic loci that contribute to increased avoidance behavior (sheltering preference). Furthermore, we showed that the quantitative trait locus (QTL) for baseline avoidance behavior on chromosome 15 is homologous with a human linkage region for bipolar disorder (8q24). Similarly, we now performed comparative analysis on the QTL for avoidance behavior found on chromosome 19 and correspondingly revealed an overlap of the mouse interval and human homologous region 10q23‐24, which has been previously linked to bipolar disorders. By means of a comparative genetic strategy within the human homologous region, we describe an association for TLL2 with bipolar disorder using the genome‐wide association study (GWAS) data set generated by the Wellcome Trust Case Control Consortium (WTCCC). On the basis of genetic homology and mood stabilizer sensitivity, our data indicate the intriguing possibility that mouse home cage avoidance behavior may translate to a common biochemical mechanisms underlying bipolar disorder susceptibility. These findings pave new roads for the identification of the molecular mechanisms and novel treatment possibilities for this psychiatric disorder, as well as for the validity of translational research of associated psychiatric endophenotypes . Abstract : By means of a comparative genetic strategy within the human homologous region, we describe an association for TLL2 with bipolar disorder.